Temporal stability of oxygen-ion conductivity in 1Nb2O5-10Sc2O3-89ZrO2. Issue 4 (April 2018) - Vandana; Singh, Shashwat; Jaiswal, Abhishek; Balani, Kantesh; Subramaniam, Anandh; Omar, Shobit
Abstract: A slight Nb2 O5 co-doping in 11Sc2 O3 -89ZrO2 was earlier reported to stabilize the high-symmetry cubic phase completely and enhances the conductivity significantly. The present work looked at the temporal stability of conductivity in 1Nb2 O5 -10Sc2 O3 -89ZrO2 (1Nb10ScSZ) for the electrolyte application in solid oxide fuel cells. In-situ conductivity measurement was done using impedance spectroscopy at 650 °C in the air for 2000 h. A substantial conductivity loss (29%) was observed in the first 1000 h. Following which, conductivity remained relatively stable for the next 1000 h. Impedance analysis showed that the main contribution to the conductivity degradation was from grain conductivity. Phase analysis performed using XRD, TEM and Raman spectroscopy revealed that both the unaged and aged 1Nb10ScSZ samples consisted of metastable t″-phase. However, the extent of tetragonality was found to increase after ageing. The formation of low-symmetry phase was suggested to be the reason for the grain conductivity loss in 1Nb10ScSZ.